Sinergitas Tiga Pilar Penjamin Mutu Pendidikan dalam Implementasi Kurikulum 2013 Melalui Proses Superfisi Akademik pada Madrasah Aliyah Sekota Metro - Umam, Aguswan Khotibul (Tapis: Jurnal Penelitian Ilmiah, 2017)
This research is intended to describe critically and qualitatively the synergy among Islamic education supervisor, head master, and Islamic education teacher in implementing 2013 curriculum through academic supervision. The data collecting techniques used in this research are observation, interview, and document review. The results of the research are (1) the supervision is conducted by Islamic education supervisor not only gradually but also incidentally through academic, administrative, and clinical supervision; (2) the academic supervision of Islamic education at MA Metro city is conducted based on qualified Islamic education supervisor, eight education quality standards, prime duty and function of Islamic education supervisor, effective madrasah management by head master, vision, mission and Islamic education strategy, and terms of reference of Islamic education supervision; 3) there are several problems that supervisor, head master, and Islamic education teacher have in implementing 2013 curriculum; 4) the synergy of quality assurance in implementing K13 must be based on maximum effort of Islamic education supervisor, head master, and Islamic education teachers at MA that are conducted according to eight terms of reference: inspecting, advising, monitoring, reporting, coordinating, and performing leadership.